Effects of Solder Temperature on Pin Through-Hole during Wave Soldering: Thermal-Fluid Structure Interaction Analysis - M. S. Abdul Aziz; M. Z. Abdullah; C. Y. Khor (The Scientific World Journal)
An efficient simulation technique was proposed to examine the thermal-fluid structure interaction in the effects of solder temperature on pin through-hole during wave soldering. This study investigated the capillary flow behavior as well as the displacement, temperature distribution, and von Mises stress of a pin passed through a solder material. A single pin through-hole connector mounted on a printed circuit board (PCB) was simulated using a 3D model solved by FLUENT. The ABAQUS solver was employed to analyze the pin structure at solder temperatures of 456.15 K (183°C) < T < 643.15 K (370°C). Both solvers were coupled by the real time coupling software and mesh-based parallel code coupling interface during analysis. In addition, an experiment was conducted to measure the temperature difference (ΔT) between the top and the bottom of the pin. Analysis results showed that an increase in temperature increased the structural displacement and the von Mises stress. Filling time exhibited a quadratic relationship to the increment of temperature. The deformation of pin showed a linear correlation to the temperature. The ΔT obtained from the simulation and the experimental method were validated. This study elucidates and clearly illustrates wave soldering for engineers in the PCB assembly industry.